Budgeting For Small Business: A Study Literature Review - Azhar, Zul; Syarif, Rini (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Small and medium-sized enterprises (SMEs) play a critical role in global economic development but often face significant challenges in managing finances, particularly in budgeting. Despite the recognized importance of budgeting in resource allocation, financial forecasting, and decision-making, its implementation in SMEs remains inconsistent, informal, and under-researched. This study presents a systematic literature review (SLR) of 137 peer-reviewed publications from 1984 to 2024 indexed in Scopus, with the aim of mapping research trends, thematic patterns, and conceptual gaps in the field of small business budgeting. Using PRISMA methodology and thematic content analysis, the review identifies five dominant themes: financial planning and control, digital budgeting tools, decision-making processes, SME-specific challenges, and risk management. The findings reveal a shift from traditional budgeting toward technology-driven and behaviorally-informed models, though gaps remain in terms of inclusivity, sustainability, and regional representation. This review contributes to the literature by offering a comprehensive synthesis of budgeting research and proposing future research directions for academics, policymakers, and SME practitioners.   Keywords: Small business; Budgeting; SME finance; Financial planning; Digital tools; Systematic literature review; PRISMA; Thematic analysis